ANALISIS PROSES KOMUNIKASI DALAM MENCEGAH KECELAKAAN KERJA DI PT. SEMEN PADANG - Dion Eriend; Azwar Azwar; Asmawi Asmawi (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This article discusses about the communication process in preventing workplace accidents at PT. Semen Padang. The communication process in preventing work accidents at PT. Semen Padang consists of primary communication processes and secondary communication processes. Communication consists of verbal and nonverbal communication. Communication occurs in one way, two ways, and multi-communication. Communicators in the prevention of workplace accidents at PT. Semen Padang is the Department of HSE, messages delivered include occupational health and safety regulations, goals and objectives and work safety and health programs, and information on potential hazards. Submission of messages is carried out through publications, socialization and occupational health and safety training. Communicators consist of employees, vendors and contractors, and other related parties. The effect of communication is increasing awareness and concern for work safety, increasing knowledge and expertise in occupational health and safety, and a positive image of PT. Semen Padang. In this process there is feedback in the form of responses, questions and input related to occupational health and safety, and other important information that is very useful for continuous improvement of the Occupational Safety and Health Management System of PT. Semen Padang. Obstacles from the communication process are Process Obstacles, Physical Barriers, Semantic Barriers, and Psychosocial Barriers.